Financing property purchase by corporate company. Case study : TH Uptown Menara Pejabat Capital Square / Nur Zulaine Mohd Shukri - Mohd Shukri, Nur Zulaine (Faculty of Architecture, Planning and Surveying, 2010)
There are various types of financing to buy property in Malaysia, especially by corporations. Among the types of financing used by corporations in Malaysia is the equity financing and debt financing. Equity financing is the capital contributed by members of the company, while debt financing is the long-term debt instruments issued by corporations to attract capital from investors. There is also a type of financing used by companies that have a large fund of cash method. This project aims to study the type of financing often used by corporations and identify the best financing should be used by corporations. The survey was conducted over a number of corporations involved including the Tabung Haji has purchase TH Uptown and Multi Purpose Holdings Berhad has purchase Menara Pejabat Capital Square. Type of financing has been used for both these companies are different which Tabung Haji has purchase TH Uptown using cash while Multi Purpose Holding was purchase Menara Pejabat Capital Square using bond and Warrant. Both types of financing have different ways and have its own advantages and disadvantages.